Diksi dan Gaya Bahasa Puisi Puisi Kontemporer Karya Sutardji Calzoum Bachri, Sebuah Kajian Stilistik - Juwati Juwati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2017)
The purpose of this study is to analyze the contemporary poetry by Sutardji Calzoum Bachri with a stylistic approach. This research is content analysis based research. The method used in this research is qualitative method. Results and discussion in this study found the elements that stand out in the development of the concept of estessstis on contemporary poetry is diction and style of language. Poets are free to play the words with the aim of beautifying poetry poems. The language style used is hyperbolic language style, repetition. Keyword: Poetry, Stylistic Approach